Morphological and phytochemical features in fruits of Pimpinella anisoides V.Brig. (Apiaceae). (2nd January 2023) - Laface, Valentina Lucia Astrid; Sicari, Vincenzo; Musarella, Carmelo Maria; Spampinato, Giovanni; Maruca, Gina; Giuffrè, Angelo Maria
Abstract: The morphological characteristics, phytochemical composition of Pimpinella anisoides fruits was investigated. The morphological analysis of the monocarps contributed to distinguish P. anisoides from other related Pimpinella species used for commercial purposes, in particular P. anisetum and P. anisum . Our study showed that these fruits are different for their surface and shape: in particular, P. anisoides monocarps are glabrous, whereas the other two species are strigose. Two main compounds were identified in the essential oil of the five studied accessions: limonene (46.78-50.74%) and anethole (38.50-42.77%) whose sum ranged between 85.28 and 93.51%. estragole and β -phellandrene were other two representative compounds. All other volatiles accounted for less than 1% of the total volatile composition. One-way ANOVA analysis showed significant differences in almost all volatiles, whereas non-significant differences were found in the compounds detected in very low quantity. Hierarchical cluster analysis allowed to group the five accessions in three main clusters. Principal Component Analysis (PCA) showed that the first two principal components explained 71.80% of total variance. Results show that morphological and phytochemical features of the ripe fruits of P. anisoides can be used to distinguish this species from others, to avoid commercial sophistications and for a better conservation.